Mining conflicts in sub-Saharan Africa: Actors and repertoires of contention - Bettina Engels (Freie Universität Berlin, Junior Research Group 'Global Change - Local Conflicts' (GLOCON), 2016)
Industrial mining is currently one of the fastest growing sectors of the world economy, particularly in the Global South. The present mining boom is, however, accompanied by numerous conflicts: conflicts over labour relations, over territorial control and access to water and land resources, over the effects on local livelihoods, on gender relations and ecological systems, and over the distribution of profits and tax revenues. In this paper, a typology of mining conflicts is developed, starting with existing case studies of current conflicts over industrial mining in sub-Saharan Africa and building on my own research in Burkina Faso. In contrast to existing typologies, the one presented here is based not on the subjects of the conflicts but on actor constellations: conflicts between trade unions and mining companies; between civil society organisations on the one hand and the state and mining companies on the other; and between artisanal miners and mining companies. I argue that historically shaped socio-ecological and socio-economic conditions, namely the existing land usages, have a crucial effect on the actors and actor constellations in conflicts over mining, and that different actors have different means of engaging in conflict at their disposal, and thus rely on different repertoires of contention when engaging in collective conflicts. – – Der industrielle Bergbau ist gegenwärtig einer der am stärksten wachsenden Wirtschaftssektoren weltweit, insbesondere im Globalen Süden. Der aktuelle Bergbau-Boom geht mit einer Vielzahl an Konflikten einher: um Arbeitsbeziehungen, um territoriale Kontrolle und den Zugang zu Wasser- und Landressourcen, um die Auswirkungen auf lokale livelihoods, auf Geschlechterverhältnisse und Ökosysteme sowie um die Verteilung der Gewinne und Steuereinnahmen. Dieses Kapitel entwickelt ausgehend von bestehenden Fallstudien zu gegenwärtigen Konflikten um den industriellen Bergbau in Subsahara-Afrika sowie aufbauend auf eigene Forschungen in Burkina Faso eine Typologie von Bergbaukonflikten. Anders als bestehende Typologien konzentriert sich diese nicht auf die Konfliktgegenstände, sondern auf die Akteurskonstellationen der Konflikte: zwischen Gewerkschaften und Unternehmen; zivilgesellschaftlichen Organisationen auf der einen und Staat und Unternehmen auf der anderen Seite; und zwischen Akteuren des handwerklichen und industriellen Bergbaus. Ich argumentiere, dass historisch geformte sozial-ökologische und sozio-ökonomische Bedingungen, insbesondere die bestehenden und vorherigen Formen der Landnutzung, wesentlichen Einfluss auf die Akteurskonstellationen in Konflikten um die Ausweitung des industriellen Bergbaus haben. Die Akteurskonstellationen wiederum bedingen die Mittel des Konfliktaustrags: Unterschiedliche Akteure haben unterschiedliche Mittel zur Verfügung und greifen entsprechend auf unterschiedliche 'repertoires of contention' in kollektiven Konflikten zurück.
Keywords: 330; mining; Africa; conflict; social movements; repertoires of contention; Bergbau; Afrika; Konflikt; soziale Bewegungen; Protestrepertoires